In Praise of Ambiguity : Erasmus, Huizinga and the Seriousness of Play - Otterspeer, W. (Book collections on Project MUSE., 2018)
In Praise of Ambiguity presents a discourse about the seriousness of play. Erasmus and Huizinga are its main characters, their books In Praise of Folly (1511) and Homo Ludens (1938) its main subject. It treats those books as contemporaries and asks what they still have to say to us. The main theme of both books is the contrast between two attitudes of life: the conviction that each subject has two or more sides as opposed to the certainty that there is always only one side to the matter. It is relativism versus essentialism, play versus seriousness. In these times of populism and fundamentalism the relationship between play and seriousness is more significant than ever. Erasmus and Huizinga conceived a compromise as brilliant as it was paradoxical: turn seriousness into play, play into seriousness. Their solution is the life blood of literature. Literature is always paradoxical, always 'true' and 'not true' at the same time, both reality and fiction. Ambiguity is its home territory. Literature is the best answer to the purity and peremptoriness of prophets.